Outcomes of Acute Appendicitis During the COVID-19 Pandemic - Ning Lu; Imad S. Dandan; Gail T. Tominaga; Frank Z. Zhao; Fady Nasrallah; James Schwendig; Hung Truong; Anthony Ferkich; Matthew R. Castelo; Dunya Bayat; Walter L. Biffl (Emergency Care and Medicine)
Background/Objectives: During the early phase of the coronavirus disease 2019 (COVID-19) pandemic, people were advised to stay at home and the American College of Surgeons suggested the nonoperative management (NOM) of uncomplicated appendicitis. We hypothesized that patients presented with more cases of complicated appendicitis during the early phase of COVID-19 compared with the previous year; we further hypothesized that more patients had NOM. Methods: Adults diagnosed with appendicitis were retrospectively reviewed from electronic medical records throughout a single county-wide hospital system. The pre-pandemic period (3 January 2019–30 June 2019, PRE) was compared with the pandemic period (3 January 2020–30 June 2020, POST). The primary outcome was AAST grade of appendicitis. Results: There were 278 cases of appendicitis in PRE and 269 in POST. The rate of complicated appendicitis (grades II–V) was higher in POST (39% vs. 30%, p = 0.0375), most prominently in the northern hospitals in the county (41% vs. 27%, p = 0.004), with non-operative management in six (3.2%) cases. Grades III–V, consistent with perforation, were seen in 33% of POST vs. 27% of PRE cases (p = 0.098). Grade I appendicitis was managed non-operatively in only six (1.6%) patients. There were fewer readmissions in POST (4% vs. 8%, p = 0.0427) and no mortalities during the study period. Conclusions: There was a significant increase in presentation with complicated appendicitis during the early phase of the COVID-19 pandemic in the northern hospitals in the county. There was no increase in NOM of uncomplicated appendicitis and no change in hospital LOS but there were fewer readmissions during COVID-19.